Doença respiratória bovina e alterações musculoesqueléticas em bovinos confinados no Brasil: uma avaliação dos aspectos de mortalidade, morbidade e prejuízos econômicos - Baptista, Anderson Lopes (2023)
Intensive beef cattle farming is a growing activity in Brazil and a way to obtain a higher quality product and increase productivity. However, as animal density increases, there is greater susceptibility to diseases or injuries due to various risk factors during the confinement cycle, such as transportation, feeding with high carbohydrate, socialization, excessive dust, and adverse environmental conditions. Among the most common diseases are bovine respiratory disease and musculoskeletal system injuries, which cause significant losses. The objetive of the present study was to evaluate the morbidity and mortality rates of confined cattle in São Paulo, Minas Gerais, Mato Grosso, Mato Grosso do Sul, Goiás, and Pará. Data were collected from 10 and 22 commercial feedlots, over periods of 2 and 5 years, totaling 699,526 and 1,972,884 animals evaluated for bovine respiratory diseases and musculoskeletal system injuries, respectively. Results showed that morbidity and mortality were higher in cattle with up to 30 days of confinement, suggesting that transport management has a negative impact. The observed morbidity rates were 3.6% and 4.97% for all diseases, with 2.08% associated with bovine respiratory disease and 1.19% with musculoskeletal system injuries. Regarding overall mortality rates, they were 0.38% and 0.57%, with 0.08% for bovine respiratory disease and 0.171% for musculoskeletal system injuries. Production losses were observed, with reduced weight gain and costs resulting from morbidity and mortality related to bovine respiratory disease, resulting in an estimated annual loss of 6.9 million USD. Hoof injuries were frequent, however, limb fractures had high lethality, both related to the rainy season. These studies investigating the incidence of two common diseases that impact beef cattle production can be used as an important reference to understand losses in local livestock production.